Strategies of Local Television Media in Maintaining Existence - Reza, Faisal; Agustin, Pramudita; Hartini Putri, Shinta; Sugiarta, Nugraha (Yayasan Sinergi Kawula Muda, 2024)
This study employs a qualitative method with a case study research approach. The subject of this research is I Channel TV Bandung, while the object is the media partnership on the Instagram account @inikpop. Informants were selected using purposive sampling. Data collection methods include observation, interviews, literature review, and documentation. Data analysis techniques involve data reduction, data presentation, and drawing conclusions. Data validity testing is conducted through source triangulation. The results of this study indicate that the partnership established through media collaboration on the Instagram account @inikpop includes cooperation in the form of advertising and promotional media publications for event organizers, building a positive corporate image through program quality and partnerships, as well as engaging with the audience to foster closeness. Media partnerships help I Channel TV maintain its existence amidst competition from online and digital media through its flagship program, INIKPOP, which also has its own promotional media channels such as Instagram, YouTube, and TikTok. In addition to media partnerships, active engagement on social media also assists I Channel TV in attracting back television audiences, who have started to decline, by presenting information content that is packaged in an engaging and distinctive manner on social media. This approach helps balance television's existence with the advancement of online media technology in people's daily lives.